PENDIDIKAN KETERAMPILAN HIDUP (LIFE SKILL) ANAK USIA DINI SELAMA MASA PANDEMI COVID-19 DI LINGKUNGAN KELUARGA - Ghata Rina; Mila Karmila (Universitas Negeri Makassar, 2020)
It is important to instill the stimulation of the child's ability to carry out self-help activities from an early age because it includes life skills that are needed to support his adulthood. This stimulation is usually implemented in Early Childhood Educationinstitutions through habituation activities, but during the Covid-19 pandemic the government enforced a school learning policy at all levels, which is usually face-to-face to learning from home (BDR). The role of parents is very crucial for the growth and development of all aspects, especially in early childhood life skills education (life skills). The purpose of this paper is to describe how life skills education can be done in the family. The research method uses literature review of various relevant references. The results of the analysis obtained data that through simple habituation such as learning discipline, independence, creativity so that it can encourage children to foster the development of early childhood life skills.